Disturbances in sleep, circadian rhythms and daytime functioning in relation to coronavirus infection and Long‐COVID – A multinational ICOSS study. (28th December 2021) - Merikanto, Ilona; Dauvilliers, Yves; Chung, Frances; Holzinger, Brigitte; De Gennaro, Luigi; Wing, Yun Kwok; Korman, Maria; Partinen, Markku; ,
Summary: This protocol paper describes the second survey produced by the International Covid Sleep Study (ICOSS) group with the aim to examine the associations between SARS‐CoV‐2 infection and sleep, sleepiness, and circadian problems as potential predisposing factors for more severe COVID‐19 disease profile and for development of Long‐COVID in the general population. The survey consists of 47 questions on sleep, daytime sleepiness, circadian rhythm, health, mental wellbeing, life habits, and socioeconomic situation before and during the pandemic, and conditional questions to those reporting having had coronavirus infection, being vaccinated, or suffering from particular sleep symptoms or sleep disorders. Surveys will be administered online between May and November 2021 in Austria, Brazil, Bulgaria, Canada, China, Croatia, Finland, France, Germany, Israel, Italy, Japan, Norway, Portugal, Sweden and USA. Data collected by the survey will give valuable information on the open questions regarding COVID‐19 disease risk factors, symptomatology and evolution of Long‐COVID, and on other long‐term consequences related to the pandemic.